2008
DOI: 10.1002/bjs.5979
|View full text |Cite
|
Sign up to set email alerts
|

Fenestrated endovascular repair for juxtarenal aortic aneurysm

Abstract: F-EVAR enabled successful treatment of juxtarenal aortic aneurysm with a low complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 11 publications
2
63
0
Order By: Relevance
“…Migration rates between 1% and 7% have been reported, 25,29 or higher in other studies, all requiring re-interventions. 85 Previous evaluation confirmed that insufficient landing zone or imprecise planning of the procedure could explain most of the adverse events, including migrations/ type I endoleak with or without visceral stent fractures.…”
Section: Endograft Migrationmentioning
confidence: 74%
See 2 more Smart Citations
“…Migration rates between 1% and 7% have been reported, 25,29 or higher in other studies, all requiring re-interventions. 85 Previous evaluation confirmed that insufficient landing zone or imprecise planning of the procedure could explain most of the adverse events, including migrations/ type I endoleak with or without visceral stent fractures.…”
Section: Endograft Migrationmentioning
confidence: 74%
“…85 Series from referral centers have included between 45 and 607 patients, with 117-1907 target vessels. 5,10,29,[32][33][34]39,80,97 Up to July 2012, a total of 2463 target vessels have been accessed through fenestrations and/or scallops, all within the use of the fenestrated Zenith SG. 20 Overall, early target vessel patency rate ranges from 90.5% to 99.7%.…”
Section: Target Vessel Stenosis/occlusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these studies, the most common causes of death were bowel ischemia (n ¼ 3) 10,11,13 and myocardial infarction (n ¼ 3). 9,15 Other causes included acute renal failure (n 10 occlusion of the internal iliac artery (n ¼ 1), 11 pulmonary embolization (n ¼ 1), 15 external iliac artery rupture (n ¼ 1), 18 acute aortic bifurcation occlusion (n ¼ 1), 18 pulmonary edema (n ¼ 1), 18 and lower limb ischemia (n ¼ 1). 19 Technical success rate.…”
Section: Primary Outcomesmentioning
confidence: 99%
“…Modular grafts are extended from an area of normal-caliber aorta in the descending thoracic aorta to a landing zone distally in either the infrarenal aorta or the bilateral iliac arteries. When there is arch involvement, it often [38] 1 1 3 2 7 Button and Jenkins [39] 1 5 0 0 Verhoeven et al [36] 3 0 2 7 [42] 90.7 19 Muhs et al [40] 9 2 4 6 Ziegler et al [43] 92.2 72 Scurr et al [44] 96.6 24 Kristmundsson et al [45] 9 6 2 5 is necessary to first perform open arch replacement using the elephant trunk procedure to provide an area in the proximal descending aorta of suitable caliber to provide a landing zone for the stent graft. Once the graft is deployed, branch vessels are cannulated through it (either through the fenestrations or the branches) and combined with small balloon-expandable covered stents to accommodate visceral arteries.…”
Section: The Proceduresmentioning
confidence: 96%